A Nitrobenzoyl Sesquiterpenoid Insulicolide A Prevents Osteoclast Formation via Suppressing c-Fos-NFATc1 Signaling Pathway - Tan, Yanhui; Ke, Minhong; Li, Zhichao; Chen, Yan; Zheng, Jiehuang; Wang, Yiyuan; Zhou, Xuefeng; Huang, Gang; Li, Xiaojuan (Frontiers in Pharmacology, 2022)
It is a viable strategy to inhibit osteoclast differetiation for the treatment of osteolytic diseases such as osteoporosis, rheumatoid arthritis and tumor bone metastases. Here we assessed the effects of Insulicolide A, a natural nitrobenzoyl sesquiterpenoid derived from marine fungus, on RANKL stimulated osteoclastogenesis in vitro and its protective effects on LPS induced osteolysis mice model in vivo. The results demonstrated that Insulicolide A inhibited osteoclastogenesis from 1 μM in vitro. Insulicolide A could prevent c-Fos and NFATc1 nuclear translocation and attenuate the expression levels of osteoclast-relatived genes and DC-STAMP during RANKL stimulated osteoclastogenesis but have no effects on NF-κB and MAPKs. Insulicolide A can also protect the mice from LPS induced osteolysis. Our research provides the first evidence that Insulicolide A may inhibit osteoclastogenesis both in vitro and in vivo, and indicates that it may have potential for the treatment of osteoclast related diseases.